Prototane-type tripternenes from the Rhizomes of Alisma plantago-aquatica - Minh, Chau Van; Kiem, Phan Van; Yen, Pham Hai; Huong, Tran Thu; Braca, Alessandra (Vietnam Journal of Chemistry, 2014)
Three terpenes with Protostane type were isolated from the rhizomes of Alisma plantago-aquatica. The chemical structures of isolated compounds were characterized as 11β,23S,24R,25-tetrahydroxyprotost-13(17)-en-3-one (alisol A, 1), 11β,23S,25-trihydroxyprotost-13(17)-en-3-one-24R-yl acetate (alisol A acetate, 2), and 11β,23S,24S-trihydroxyprotost-13(17),25-dien-3-one (alisol G, 3), by detailed analysis of the 1D- and 2D-NMR spectra such as 1H-, 13C-NMR, DEPT 90, DEPT135, HSQC, HMBC, 1H-1H COSY, and by the Electronspray Ionization (ESI) mass spectrum. This is the first report of alisol G from Alisma plantago-aquatica